Improving collaborative problem solving skills in 7th grade junior high school students through science learning based on creative problem solving models - Yasir, Mochammad; Wulandari, Ana Yuniasti Retno; Awaliyah, Nur Irmiyanni (JIPVA (Jurnal Pendidikan IPA Veteran); Vol 7 No 1 (2023): JIPVA (Jurnal Pendidikan IPA Veteran), 2023)
Collaborative problem solving skills are one of the key skills of the 21 st century. Students have difficulty working together to solve problems because studying the science appears to be cooperative and less geared towards having direct experience. There is a need for efforts to make studying the science meaningful. The aims of this research were to find out: 1) the differences in collaborative problem solving skills of junior high school students before and after the implementation of the creative problem solving (CPS) model, and 2) to improve collaborative problem solving skills through science learning based on the CPS model in 7 th grade junior high school. This study was conducted at one of East Java’s state junior high schools. A one group-pretest-posttest design was study method used. Purposive sampling with a sample size of 32 students was used for the sample selection technique. Using paired t-test and n-gain data analysis. The findings showed that (1) there was a difference before and after the implementation of the CPS model with paired t test results obtained -5,175 or 2,232 or 5,175, and (2) there was an improvement in collaborative problem-solving skills of junior high school students with 0.34 classified moderate n-gain tests. It can be inferred on the basis of the research results that the CPS model can improve collaborative problem-solving skills in junior high school students in class VII.